Toxic Masculinity Dalam Sistem Patriarki: Analisis Wacana Kritis Van Dijk Dalam Film Story Of Kale - Yuyun, Yuyun; Wardiah, Dessy; Hetilaniar, Hetilaniar (ANTHOR: Education and Learning Journal, 2022)
Patriarchy means the position of men as the center, the sole entrepreneur. This film was researched to raise the problems experienced by women, according to a study, the problems that most often occur in the private sphere, namely dating violence. This study aims to identifyand describe the critical discourse found in the film Story Of Kale (2020) by Teun Van Dijk. In this study, researchers used Van Dijk's Critical Discourse Analysis in the dimensions of text which included macro structure, superstructure, and microstructure. The type of research used is the descriptive qualitative method. The source of the data in this research is the film Story Of Kale. The method used to collect data is documentation. The data collection technique uses content analysis techniques, then the data validation technique used is source triangulation. From the results of research in the text dimension which includes macro structure, superstructure, and microstructure, it is found that intertwined relationships are found in highlighting toxic masculinity as a form of negative masculinity in a patriarchal system, the domination relation to an unhealthy relationship is woven by Argo and Kale towards Dinda.